If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x-3)+8=2x+3(-1+x)
We move all terms to the left:
5(x-3)+8-(2x+3(-1+x))=0
We add all the numbers together, and all the variables
5(x-3)-(2x+3(x-1))+8=0
We multiply parentheses
5x-(2x+3(x-1))-15+8=0
We calculate terms in parentheses: -(2x+3(x-1)), so:We add all the numbers together, and all the variables
2x+3(x-1)
We multiply parentheses
2x+3x-3
We add all the numbers together, and all the variables
5x-3
Back to the equation:
-(5x-3)
5x-(5x-3)-7=0
We get rid of parentheses
5x-5x+3-7=0
We add all the numbers together, and all the variables
-4!=0
There is no solution for this equation
| 47=x | | (2x+6)(x+2)=0 | | n/3+12=15 | | -4d+4=-3+3d | | 10=w+2 | | (x+12)(x+4)=0 | | -4d+4=-33d | | 5(x-3)+8=3(-1+x) | | 4(x-1)+x+8=3x-2 | | -6+7j=10+9j | | -8+8z+6=8+7z | | x2=108. | | (2x+12)(2x+4)=0 | | (2x+7)(2x+4)=0 | | 10+8f=10f | | 3/4m=17 | | -7h-6=2-8h | | x2=45. | | 7b-2=8+6b | | (3x)+4=5 | | 3x÷4=2.5x | | 5e-7=18 | | -8w-10=-3w | | 54=x | | 3x-8=-7x | | -8+2d=4d | | x-15/5=27 | | 3x-4=2.5× | | -2q+7=-q | | 148-u=215 | | -10m-10=-9m | | -2.3+y/5=-14.8 |